STRATEGI PENGHINDARAN PAJAK DAN KUALITAS LAPORAN KEUANGAN: PERAN LEVERAGE SEBAGAI PEMODERASI - Herwanda, Reyhan; Firmansyah, Amrie (APSSAI, 2024)
This study aims to determine the effect of tax avoidance on the quality of financial reporting using leverage as a moderating variable. In this study, the quality of financial reporting, as the dependent variable, uses the Beneish M-Score, and tax avoidance, as the independent variable, uses the effective tax rate (ETR). The sample of this study uses manufacturing companies listed on the Indonesia Stock Exchange from 2021-2023. Using purposive sampling, this study uses 19 companies with 57 observations. This study uses a quantitative approach with multiple linear regression analysis for panel data. The results show that tax avoidance positively affects financial reporting quality, and leverage weakens the positive effect of tax avoidance on the quality of financial reporting. This study recommends that accounting standard setters create standards that can prevent the practice of manipulating financial statements.